From domestic women to sensitive young men translating the individual in early colonial Korea - Yang, Yoon Sun (Harvard East Asian monographs, 2017)
Examines how the European notion of the individual put down its roots in Korean literature, especially through literary figures, in the early twentieth century. Using Korean literary examples, it calls into question the belief that there is only one kind of individuality transferable across cultural, temporal, and gender boundaries."--Provided by publisher.